2017
DOI: 10.2474/trol.12.58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Couple Stress Lubrication on Symmetric Hole-Entry Hybrid Journal Bearing

Abstract: The present study deals with capillary compensated symmetric hole-entry hybrid journal bearing under couple stress lubricant. Reynolds equation has been modified considering couple stress lubricant in the bearing system. The Galerkin's Technique has been applied to solve the modified Reynolds equation together with restrictor flow equation. The computation of bearing performance has been made by using couple stress parameter. The bearing operating with couple stress lubricant provides better values of fluid fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The bearing flow was reduced for couple stress fluid lubricated non-circular journal bearing. Ram [37] compared symmetric and asymmetric journal bearings under couple stress lubrication. It was found that couple stress lubricant provided the enhancement in minimum fluid film thickness, stiffness and damping coefficients at constant load.…”
Section: Couple Stress Lubricantsmentioning
confidence: 99%
“…The bearing flow was reduced for couple stress fluid lubricated non-circular journal bearing. Ram [37] compared symmetric and asymmetric journal bearings under couple stress lubrication. It was found that couple stress lubricant provided the enhancement in minimum fluid film thickness, stiffness and damping coefficients at constant load.…”
Section: Couple Stress Lubricantsmentioning
confidence: 99%
“…Also, Bansal et al [22] highlighted elastic distortion effects on stability of micropolar lubricated hydrodynamic bearing and their results indicated that increase in flexibility causes decrease in stability. Various studies concerning the theory of micropolar lubricant and effects of micropolar parameters on performance and stability of journal bearings have also been reported in literature [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%